2007
DOI: 10.1159/000105124
|View full text |Cite
|
Sign up to set email alerts
|

TGF-Beta1 Release by Volatile Anesthetics Mediates Protection against Renal Proximal Tubule Cell Necrosis

Abstract: Background/Aims:We have previously demonstrated that clinically utilized volatile anesthetics protect against renal ischemia reperfusion injury in rats in vivo and reduce necrosis in vitro via activation of ERK and Akt and by upregulating HSP70. In this study, we further deciphered the upstream cellular signaling mechanism(s) of volatile anesthetic-mediated antinecrotic effects in vitro. We hypothesized that volatile anesthetics perturb the structure of the plasma membrane lipid bilayer, causing externalizatio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
57
0
1

Year Published

2009
2009
2022
2022

Publication Types

Select...
10

Relationship

2
8

Authors

Journals

citations
Cited by 56 publications
(61 citation statements)
references
References 58 publications
3
57
0
1
Order By: Relevance
“…16,49 Volatile Anesthetics Release Renal Tubular TGF-b1 and Promote Plasma Membrane Caveolae Formation Disruption of the plasma membrane lipid bilayer by volatile anesthetics results in the translocation of phosphatidylserine from the inner leaflet to the outer leaflet of the plasma membrane (Figure 3). 50 Phosphatidylserine (PS) externalization in macrophages as well as in renal tubular epithelia leads to the release of a potent anti-inflammatory/antinecrotic molecule TGF-b1 in adjacent cells via ligation of PS receptors. 41,51,52 Indeed, TGF-b1 has been recognized as a key signaling molecule in the anti-inflammatory milieu of macrophages ingesting apoptotic cells.…”
Section: Volatile Anesthetics and Renal Protection Mechanismsmentioning
confidence: 99%
“…16,49 Volatile Anesthetics Release Renal Tubular TGF-b1 and Promote Plasma Membrane Caveolae Formation Disruption of the plasma membrane lipid bilayer by volatile anesthetics results in the translocation of phosphatidylserine from the inner leaflet to the outer leaflet of the plasma membrane (Figure 3). 50 Phosphatidylserine (PS) externalization in macrophages as well as in renal tubular epithelia leads to the release of a potent anti-inflammatory/antinecrotic molecule TGF-b1 in adjacent cells via ligation of PS receptors. 41,51,52 Indeed, TGF-b1 has been recognized as a key signaling molecule in the anti-inflammatory milieu of macrophages ingesting apoptotic cells.…”
Section: Volatile Anesthetics and Renal Protection Mechanismsmentioning
confidence: 99%
“…Immunohistochemistry for huA 1 ARs was performed as described below. Finally, total RNA was extracted from renal cortices or liver and we performed reverse transcription-PCR assays for EGFP-huA 1 AR, EGFP and mouse GAPDH as described previously 14,17,18 (Table 1). The EGFP-huA 1 AR primer was designed with a sense primer that would anneal in the extreme 5 0 end of the A 1 AR portion of the construct, whereas the anti-sense primer anneals to the extreme 3 0 end of the EGFP portion.…”
Section: Determination Of Transgene Expression With Intrarenal Lentivmentioning
confidence: 99%
“…Simultaneously, ACEI might enable activity of bradykinin to last long and alter renal hemodynamics, delaying fall of glomerular filtration rate (GFR) (37). Moreover, the interdiction of RAS by ACEI was suggested to restrain production and activity of TGF-β1 within nephridial tissues, which caused sclerosis and fibrosis of glomerular (38)(39)(40). Clinical studies also confirmed the meaningful role of ACEI (eg, benazepril and captopril) in doubling blood creatinine levels and improving prognosis of DN patients (41).…”
Section: Discussionmentioning
confidence: 96%